Absence and Ambiguity: Documenting the Moment of Birth in East Lombok, Indonesia - Butt, Leslie (Anthropologica, 2018)
Birth registration has become prominent among global initiatives to “leave no one behind.” Despite Indonesia's efforts to implement a national registration program, low-income rural families in East Lombok do not choose to register their children in significant numbers. By closely examining the documents and documentary practices linked to childbirth, this article unpacks the ambiguous meanings the Indonesian government and the Sasak of East Lombok hold around childbirth. Sasak family engagement with existing birth rituals highlights the exceptional convergences required to create documentary links between place, person and nation.